The Effect of Household Air Pollution Exposure on the Incidence of Acute Respiratory Infection in Children Under Five in Asia: A Meta-Analysis (Global Health Science Group, 2023)
ASIA is a continent with many people who still have and use biomass or solid fuel use (SFU) for cooking and various household air pollution. Previous research has mentioned the negative effects of household air pollution on the incidence of acute respiratory infections in children under 5 years. Acute respiratory diseases have even become the cause of at least 4 million deaths of children under 5 years old every year in the world. The meta-analysis aimed to estimate the correlation between household air pollution and the incidence of acute respiratory infections in children under five in ASIA. This study was a meta-analysis. Primary data is taken through the electronic databases such as: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords